Association between psychological resilience and subjective well-being in older adults living with chronic illness. Issue 4 (2nd October 2019) - Tecson, Kristen M.; Wilkinson, Lindsay R.; Smith, Bethany; Ko, Jong Mi
Abstract: We aimed to determine the impact of resilience on well-being in chronically ill adults, hypothesizing that resilient participants would have higher quality of life, life satisfaction, and happiness and less psychological distress than those with low resilience. Patients who received treatment for a chronic illness at Baylor Scott & White Health and self-identified an informal caregiver (nonpaid friend/family member who provides regular care) were eligible. After the Center for Community Research and Development administered a phone survey from March to June 2017, we built linear and ordinal logistic regression models to assess the effect of resilience on well-being while adjusting for health, finances, marital status, and gender. Forty-one participants completed the study. The average age was 67 ± 10 years; the most common illness was heart failure (39%). Participants had high resilience (median 4 [quartile 1 = 3, quartile 3 = 5], scale: 1–5), low psychological distress (4 [2, 7], scale: 0–24), high quality of life (8 [5, 9], scale: 0–10) and life satisfaction (5 ± 2, scale: 1–7), and 81% were pretty/very happy. The effect of resilience was significant in the expected directions in unadjusted analyses. After accounting for demographic, social, and clinical factors, resilience remained highly significant for psychological distress and happiness ( b = –1.91, P = 0.002; odds ratio = 4.71, P = 0.003, respectively). Psychological resilience may be a resource to preserve well-being for chronically ill individuals.